Pemantauan DJJ dengan Bantuan Dopler pada Ibu Hamil Ny. “H” umur 22 tahun G1P0A0 Sejak Usia Kehamilan 31 minggu 4 Hari Secara Komprehensif - Arini, Arini; Nurasmi, Nurasmi; hutagaol, Iin octaviana (Indonesia Berdaya, 2024)
The infant mortality rate in Indonesia reaches 35 per 1000 live births, while neonatal mortality (0-28 days) is 19 per 1000 live births. These figures are much higher compared to neighboring countries. The aim of this study is to provide comprehensive midwifery care by utilizing a Doppler device to monitor the fetal heart rate (FHR) in a pregnant woman, Mrs. "H," aged 22, G1P0A0, from 31 weeks and 4 days of pregnancy. The type of research used is descriptive with a case study approach, specifically describing the results of FHR monitoring from pregnancy until delivery, documenting the examination results. This study was conducted at the Kawatuna Health Center in Palu City from March 4, 2024, to April 26, 2024. Periodic FHR monitoring was performed using a Doppler device. The research methodology included assessment, formulation of diagnoses and midwifery problems, planning, implementation, and evaluation. The results showed that the FHR was within normal limits, ranging from 134 beats per minute to 148 beats per minute. Regular FHR monitoring should be performed by midwives to ensure the fetus is in good condition.